Leukotrienes as Modifiers of Preclinical Atherosclerosis? - Graziano Riccioni; Magnus Bäck (The Scientific World Journal)
Preclinical atherosclerosis represents a crucial period associated with several pathophysiological reactions in the vascular wall. Failure to diagnose preclinical atherosclerosis at this stage misses a major opportunity to prevent the long-term consequences of this disease. Surrogate biological and structural vascular markers are available to determine the presence and the extension of preclinical vascular injury in the general population. Examples of surrogate markers are carotid intima media thickness and biomarkers including high-sensitivity C-reactive protein, cell adhesion molecules and matrix metalloproteinases, and leukotrienes. Recently, leukotrienes have been implicated as mediators, biomarkers, and possible therapeutic targets in the context of subclinical atherosclerosis. The aim of this short paper is to focus on the relation between preclinical atherosclerosis and leukotrienes, with particular attention to the recent development on the use of leukotriene modifiers in the treatment of atherosclerosis.